Python based GIS tools for landscape genetics: visualising genetic relatedness and measuring landscape connectivity - Etherington, Thomas R. (Methods in ecology and evolution, 2011)
Summary 1. Landscape genetics is an area of research that can help to understand many spatial ecological processes, but requires significant interdisciplinary collaboration. Use of geographic information system (GIS) software is essential, but requires a degree of customisation that is often beyond the non‐specialist. 2. To help address this, a series of Python script based GIS tools have been developed for use in landscape genetics studies. 3. The scripts convert files, visualise genetic relatedness, and measure landscape connectivity using least‐cost path analysis. The scripts are housed in an ArcToolbox that is freely available along with the underlying Python code. 4. The Python scripts allow researchers to use more current software, provide the option of further development by the user community, and reduce the amount of time that would be spent developing common solutions.